THEME SYSTEM OF SYSTEMIC FUNCTIONAL GRAMMAR IN STUDENTS' NARRATIVE TEXTS - Safitra, Zuhe (2013)
This study aims to explore the realization of the Theme system in students' narrative texts in terms of types of Theme, choices of topical Theme and thematic progressions. The study also attempts to find out the implications of the Theme system on the flow of text. The study belongs to a non-experimental research design involving 15 narrative texts as the data of the study. There were three types of Theme used by the students, namely topical, textual and interpersonal Themes, in which the topical Theme was the most frequent Theme (65.12%) used. In terms of choices of topical Theme, there were ten categories realized in the texts, and of the ten, the nominal group was the most frequent category (35.57%) chosen by the students as their topical Theme. Derived from the realization of thematic progressions, there were three kinds of pattern used by the students, which are the thematic reiteration pattern, the zig-zag pattern and the multiple-Rheme Pattern. The thematic reiteration pattern was the most common pattern (60.57%) found in the texts. These findings suggest that the texts produced by the students were smoothly flowing, indicated by the frequent use of the thematic reiteration and zig-zag patterns. The use of the cohesion devices (i.e. ellipsis, reference, and conjunction) also made the flow of the text much clearer. It is recommended that Theme system be implemented in teaching English at high school level to improve students' reading and writing skills and to develop the depth of their writing. Keywords: Theme System, Narrative Text, Flow of the Text